2021
DOI: 10.1093/braincomms/fcab190
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of [18F]PI-2620, a second-generation selective tau tracer, for assessing four-repeat tauopathies

Abstract: Tau aggregates represent a key pathologic feature of Alzheimer’s disease and other neurodegenerative diseases. Recently, PET probes have been developed for in vivo detection of tau accumulation; however, they are limited because of off-target binding and a reduced ability to detect tau in non-Alzheimer’s disease tauopathies. The novel tau PET tracer, [18F]PI-2620, has a high binding affinity and specificity for aggregated tau; therefore, it was hypothesized to have desirable properties for the visualization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 51 publications
1
59
0
Order By: Relevance
“…Clinical studies, however, were not able to find a consistent binding to non-AD tau. Moreover, there was no postmortem correlation to tau pathology in a CBD case (244). However, in another study using a dynamic technique, [18F]-PI-2620 was able to differentiate PSP-RS from healthy controls, PD, MSA, and non-RS PSP (245) and in a follow-up study, an improved imaging technique was proposed (246).…”
Section: Positron Emission Tomographymentioning
confidence: 98%
“…Clinical studies, however, were not able to find a consistent binding to non-AD tau. Moreover, there was no postmortem correlation to tau pathology in a CBD case (244). However, in another study using a dynamic technique, [18F]-PI-2620 was able to differentiate PSP-RS from healthy controls, PD, MSA, and non-RS PSP (245) and in a follow-up study, an improved imaging technique was proposed (246).…”
Section: Positron Emission Tomographymentioning
confidence: 98%
“…150 A recent study using autopsy-confirmed AD and non-AD tauopathies, however, revealed that [18F]PI-2620 retention was not correlated with tau burden at postmortem pathological assessment. 151 [18F]PM-PBB3 is another second-generation tau PET tracer, which has great promise to visualise pathological tau aggregates in AD and non-AD tauopathies. 139 The retention of [18F] PM-PBB3 was increased in the primary motor cortex, basal ganglia, brainstem and middle frontal gyrus in a patient with CBD confirmed by brain biopsy.…”
Section: Tau Petmentioning
confidence: 99%
“…Furthermore, non-invasive static [18F]PI-2620 PET scans during this period provides comparable quantification accuracy to dynamic scans with arterial sampling in this cohort [74] . Although these are the optimal conditions for [18F]PI-2620 PET in AD, recent work has found that [18F]PI-2620 tracer kinetics differ in 4R-tauopathies, presenting with earlier peaks than in AD [80] .…”
Section: Imaging Pathological Taumentioning
confidence: 99%
“…Another area of investigation in tau PET imaging is the appropriate acquisition time and measurement parameters for these tracers. As evidenced by the work with [18F]PI-2620, the optimal time windows in AD versus non-AD tauopathies may differ [80] , [85] , [99] . Overall, standardized uptake value ratio (SUVR) and DVR are the most common parameters for describing the binding patterns of these tau PET tracers in the brain.…”
Section: Challenges For Pet Imagingmentioning
confidence: 99%